KAJIAN PERKEMBANGAN PENDIDIKAN ASTRONOMI UNTUK SMA DI INDONESIA - Rahmi Elzulfiah; Diba Efriza Mahanti; Fahmi Ramadhan; Hadi Nasbey (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
The main aimed of this study is to review development of Astronomy Education in Senior High School. Prestigious event, such as the Nasional Science Olympiad (OSN) or Internasional Astronomy Olympiad, any high school students must have good Astronomy’s skill and knowledge to be eligible as the champion in the city/regency, province, national, or international level olympiad. Based on Bloom’s taxonomy, Basic Competence of Astronomy in the high school curiculum is at C5 level, but it is about matematical vector aplication for Newton’s law of gravity. It sugests a gap in the curiculum. So that, it becomes one of the causes of uneven education in Indonesia. Therefore, only apart of students, who have apropriate tools, a reliable teacher, and supported situation, who can compete well. This paper is expected to provide some solutions in equalization of astronomy means and knowledge for any high school’s students. Keywords:Astronomy Education, Curiculum, Astronomy Olympiad.